Motivation to learn Japanese as a foreign language in an English speaking country: An exploratory case study in New Zealand. (February 2019) - de Burgh-Hirabe, Ryoko
Abstract: The conceptualization of L2 motivation has largely involved survey-only studies of English, a growing global language, in English as foreign language (EFL) contexts. There has been less consideration of languages other than English, such as Japanese. This study aims to understand the motivation types and learning experiences of Japanese as a foreign language (JFL) learners in New Zealand, where foreign language learning is neither required nor widely valued, and where JFL learner numbers have declined at universities. This small-scale exploratory semester-long study examines different motivational constructs through qualitative data from an open-ended questionnaires and quantitative data from an L2 motivation survey. Analysis of the data indicated that integrativeness was the major initial reason for choosing to learn Japanese, but as students engaged in JFL learning and with the L2 community, they developed ideal L2 selves. Positive L2 learning experiences, often related to intrinsic orientation to learning, sustained their JFL learning. This study draws a different picture to previous EFL motivation research about future self-images, showing that different target languages and diverse reasons for learning should be considered in analyzing L2 motivation.